PENGARUH PENERAPAN BUDAYA SEKOLAH ISLAMI TERHADAP KARAKTER RELIGIUS SISWA DI SMP NEGRI 2 BUKITTINGGI - Mutiara Diva Siregar; Yulia Rahman, Alimir, Fenny Ayu Monia (CV. ADIBA AISHA AMIRA, 2024)
This research focuses on Islamic school culture on the religious character of students at SMP N 2 Bukittinggi. Schools need to realize how important the role of Islamic school culture is in shaping students' religious character. Considering that there are various personality deviations among students, through Islamic school culture it is hoped that students can develop their personalities through the habits carried out at school. The formulation of the problem in this research is how Islamic school culture influences the religious character of students at SMP N 2 Bukittinggi. The aim of this research is to explain the influence of the role of Islamic school culture on the religious character of students at SMP N 2 Bukittinggi. This research method is quantitative and with a causality design with a sample size of 75 students determined using random probability sampling techniques. The instrument used was a questionnaire with student respondents. The data collection tool uses a questionnaire on Islamic school culture and religious character. With a correlation coefficient value of 0.406, meaning it has a positive influence and the coefficient of determination R Squer is 0.165, which means the influence of Islamic school culture on religious character is 16.5% while the remainder is 83.5%. % influenced by other factors. The results of this research analysis show that there is a positive and significant influence between Islamic school culture on students' religious character.